2022
DOI: 10.3390/healthcare11010014
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Smartphone Addiction among University Students in South Korea: A Systematic Review

Abstract: Background: Globally there has been an exponential increase in the penetration of smartphones among the youth population and smartphones have become indispensable in the daily lives of university students in South Korea. Several studies have associated the problematic use of smartphones or addiction with different adverse outcomes. The goal of this study was to collate empirical evidence and provides an overall synthesis of the literature about the adverse effects of smartphone addiction on university students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…These findings contradict the results of another study, which indicated that bachelor's degree students were more addicted to smartphones [27]. University students are the age group most interested in using smartphones for various activities such as studying, entertainment, accessing the Internet or social networks, and social communication [28]. It is possible that master students use smartphones more because they have more ability to use the Internet and search for information than bachelor students.…”
Section: Discussionmentioning
confidence: 62%
“…These findings contradict the results of another study, which indicated that bachelor's degree students were more addicted to smartphones [27]. University students are the age group most interested in using smartphones for various activities such as studying, entertainment, accessing the Internet or social networks, and social communication [28]. It is possible that master students use smartphones more because they have more ability to use the Internet and search for information than bachelor students.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, smartphone addiction predicts self-control, academic burnout, social anxiety, and perceived social support in university students, consistent with previous studies. Achangwa et al [ 87 ] found that smartphone addiction among university students negatively affects their physical, mental, and emotional health, academic performance, and social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was also reported that global smartphone penetration was around 41.5% (Ertemel & Ari, 2020). Achangwa et al (Achangwa, Ryu, Lee et al, 2022) recently reported that nearly 97% of the Korean population was penetrated with a smartphone with 100% of the penetration rate achieved in younger people between the ages of 20 and 30. Besides, half of the teenage population reported that they believe themselves addicted to smartphones (Cohen, 2016).…”
mentioning
confidence: 95%